Pain Relieving Effect of Intraoperative Chemical Splanchnicectomy of Celiac Ganglions in Patients with Resectable Pancreatic or Gastric Masses: A Randomized Clinical Trial - Jalal Vahedian; Amir Saraee; Massoud Baghai Wadji; Saeed Safari; Abdolhamid Chavoshi Khamneh (Pain Research and Management)
Background. Trials of intraoperative chemical splanchnicectomy during resection of pancreatic and gastric masses resulted in significant difference in a patient’s postoperative pain. This study aims to determine if splanchnicectomy by alcohol neurolysis can relieve postoperative pain after gastrectomy and Whipple surgery. The study explores differences in outcomes at first four months after surgery. Methods. Fifty-eight patients with gastric and 60 patients with pancreatic resectable masses were included (28 were lost to follow-up). Each randomized in control and intervention subgroups. Intervention subgroups underwent chemical blockage of celiac ganglions by ethanol injection at both sides of suprapancreatic aorta. Participants were asked to report their pain intensity according to the Visual Analogue Scale (VAS) at specific times. Result. The overall postoperative pain of injected Whipple and gastrectomy subgroups was lower than the noninjected Whipple and gastrectomy subgroups (p<0.001). The pain-modifying effect of the injection was not different between Whipple and gastrectomy groups (p=0.125) Conclusion. Splanchnicectomy is recommended for pain reduction after abdominal operations. Perspective. This article presents positive effect of intraoperative chemical splanchnicectomy during resection of pancreatic and gastric masses on postoperative pain. This is an easy, effective, safe, and inexpensive procedure recommended for all operable gastric or pancreatic masses to palliate the pain degree.